2013
DOI: 10.3389/fnins.2013.00194
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy to protect and repair the developing brain: a review of mechanisms of action of cord blood and amnion epithelial derived cells

Abstract: In the research, clinical, and wider community there is great interest in the use of stem cells to reduce the progression, or indeed repair brain injury. Perinatal brain injury may result from acute or chronic insults sustained during fetal development, during the process of birth, or in the newborn period. The most readily identifiable outcome of perinatal brain injury is cerebral palsy, however, this is just one consequence in a spectrum of mild to severe neurological deficits. As we review, there are now cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 143 publications
(174 reference statements)
1
81
0
2
Order By: Relevance
“…In the neurologic field, many paracrine effects related to neurogenesis, myelination, angiogenesis, synaptogenesis, apoptosis, etc. have been demonstrated [5]. Although MSCs are generally isolated from BM or CB, these cells have also been reported to exist in PB.…”
Section: Mscs Vs Mncs For Cell Therapymentioning
confidence: 99%
“…In the neurologic field, many paracrine effects related to neurogenesis, myelination, angiogenesis, synaptogenesis, apoptosis, etc. have been demonstrated [5]. Although MSCs are generally isolated from BM or CB, these cells have also been reported to exist in PB.…”
Section: Mscs Vs Mncs For Cell Therapymentioning
confidence: 99%
“…Their discovery led to the new concept of vasculogenesis [96] ; this is the development of new blood vessels by the recruitment and maturation of EPCs, in contrast to angiogenesis whereby new blood vessels are formed from proliferation of the pre-existing endothelium. Thus, it was hypothesized that harnessing the potential of EPCs in promoting neovascularization in the presence of ischaemic injury [97] would be valuable as a novel therapeutic intervention [98] . Indeed, several studies which have begun to assess the impact of the activation of EPCs in the presence of ischaemic injury have demonstrated that EPC treatment reduces infarct volume, improves deficits in cognitive learning and motor skills, and is associated with the recovery of regional cortical blood flow [99,100] .…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…Stem cells differentiate into neurons, oligodendrocytes and astrocytes which replace and repair the white matter injury in CP [17] (Figure 2). The growth factors secreted by these cells also help in remyelination, synaptogenesis, cytoprotection and angiogenesis which reverse the cellular injury in CP [18,19].…”
Section: Stem Cell Therapy In Cerebral Palsymentioning
confidence: 99%